Factors influencing premature ovarian insufficiency: a systematic review and meta-analysis - Shuling Lin; Shanyan Chen; Qin Zhang (Journal of Obstetrics and Gynaecology)
Background Premature ovarian insufficiency (POI) has multiple contributing factors. This study aims to systematically evaluate these factors and their mechanisms, identify high-risk groups, support early intervention, and provide a basis for future research.Methods Following the PRISMA guidelines, a search was conducted across 11 Chinese and English databases, including PubMed, Embase, and the Cochrane Library, up to January 2024. Observational studies on patients with ovarian insufficiency were included. A meta-analysis using Stata 14 was performed to calculate odds ratios (OR) and 95% confidence intervals (CIs) for factors influencing POI.Results A total of 38 studies with 4,968 cases and 5,158 controls were included. The following factors were identified as risk factors for POI: abnormal menstruation (OR = 2.707, 95% CI: 1.705–4.299), hair dyeing (OR = 4.725, 95% CI: 2.914–7.660), chemical exposure (OR = 3.314, 95% CI: 2.283–4.811), Type A personality (OR = 6.106, 95% CI: 4.696–7.939), survival stress (OR = 3.292, 95% CI: 2.380–4.555), sleep deprivation (OR = 3.340, 95% CI: 2.363–4.721), bad mood (OR = 4.654, 95% CI: 2.783–7.781), smoking history (OR = 2.748, 95% CI: 1.928–3.917), family history of POI (OR = 4.338, 95% CI: 2.422–7.768), history of mumps (OR = 5.802, 95% CI: 3.460–9.730), number of abortions (OR = 2.292, 95% CI: 1.887–2.785), and history of pelvic surgery (OR = 4.836, 95% CI: 3.066–7.628). Physical exercise (OR = 0.270, 95% CI: 0.106–0.692) and vegetable intake (OR = 0.434, 95% CI: 0.337–0.560) were protective factors. Sensitivity analysis and publication bias tests confirmed robustness.Conclusions POI is related with abnormal menstruation, hair dyeing, chemical exposure, Type A personality, survival stress, sleep deprivation, bad mood, smoking history, family history of POI, history of mumps, number of abortions, and history of pelvic surgery. Physical exercise and vegetable intake may provide protection. These findings inform clinical strategies for early identification and management.